2018
DOI: 10.1371/journal.pone.0198144
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma angiotensin converting enzyme 2 activity is an independent predictor of major adverse cardiac events in patients with obstructive coronary artery disease

Abstract: BackgroundAngiotensin converting enzyme 2 (ACE2) is an endogenous regulator of the renin angiotensin system. Increased circulating ACE2 predicts adverse outcomes in patients with heart failure (HF), but it is unknown if elevated plasma ACE2 activity predicts major adverse cardiovascular events (MACE) in patients with obstructive coronary artery disease (CAD).MethodsWe prospectively recruited patients with obstructive CAD (defined as ≥50% stenosis of the left main coronary artery and/or ≥70% stenosis in ≥ 1 oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
153
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(162 citation statements)
references
References 35 publications
6
153
0
3
Order By: Relevance
“…The clinical implication of circulating ACE2 appears complex. For example, although previous observational studies [32][33][34] determined that increased ACE2 activity was associated with poor outcome, in a study involving patients after intensive treatment for acute CHF, 65…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical implication of circulating ACE2 appears complex. For example, although previous observational studies [32][33][34] determined that increased ACE2 activity was associated with poor outcome, in a study involving patients after intensive treatment for acute CHF, 65…”
Section: Discussionmentioning
confidence: 99%
“…In 1 such study, 31 serum ACE2 activity was significantly increased secondary to ischemic and nonischemic heart disease and was independent of medications or comorbidities. In other studies, [32][33][34] portions of the cell membrane, which then are released into the surrounding extracellular space. 33,35,36 The resultant ectosomes contain ACE2 as well as the immediate surrounding extracellular environment and enter the circulation or urine.…”
Section: Discussionmentioning
confidence: 99%
“…In-vitro models free of COVID-19 reported that ACEi and ARB treatment increased membrane expression of ACE2, especially in the heart (9,16,35). In-vitro findings in the few human studies of healthy (COVID-19-free) subjects were discordant (36)(37)(38)(39). It should also be borne in mind that circulating ACE2 levels may not match membrane expression and tissue activity (the latter possibly varying depending on the tissue).…”
Section: -Acei-arb and Covid-19mentioning
confidence: 97%
“…Therefore, ACE2 functions as a counterbalance to its structurally similar counterpart ACE [53] through the conversion of Ang II into Ang-(1-7), which in contrast to ACE, promotes vasodilation, reduces proliferation, and prevents apoptosis. [53] ACE2 levels are known to be low in healthy individuals [54] and ACE2 levels decrease with age. [55] Chronically elevated levels of ACE2 are an independent predictor of disease progression; but evidence suggests these changes are compensatory rather than causal.…”
Section: Angiotensin II / At 1 Receptor Relationshipmentioning
confidence: 99%